A revision of Sclerochiton (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2011)
Based on a revision of the available types and of additional material, fifteen species of Sclerochiton Kraatz, 1859 are recognized in the Oriental region and the adjacent south of the East Palaearctic. All the species are (re-)described and illustrated, twelve of them for the first time: S. acutissimus sp. n. (China: Sichuan); S. barbatus sp. n. (China: Yunnan); S. bistipulatus sp. n. (southern India); S. excisus sp. n. (Malaysia); S. hastatus sp. n. (northern Pakistan, northern India); S. laoticus sp. n. (Laos); S. maculosus sp. n. (China: Yunnan); S. penicillatus sp. n. (Nepal); S. rectus sp. n. (Thailand); S. rougemonti sp. n. (Thailand); S. schuelkei sp. n. (China: Yunnan); S. sinuatus sp. n. (Thailand, Myanmar). The genus is redescribed and attributed to the subtribe Astenina. It has a discontinuous distribution with six species in the Afrotropical region and fifteen species in the Oriental region and the adjacent south of the East Palaearctic. In the study region, the diversity is highest in China, India, and Thailand (five species each), and Nepal (three species). The species were collected from forest litter at low to intermediate altitudes (150-2400 m). Adult beetles have been found throughout the year. A key to species and a catalogue are provided. A new synonymy is proposed: Echiaster unicolor Bernhauer, 1922 = E. japonicus Bernhauer, 1923, syn. n. Keywords Coleoptera, Staphylinidae, Paederinae, Astenina, Sclerochiton, Echiaster, Palaearctic region, Oriental region, taxonomy, new species, new synonymy, key to species, catalogue, discontinuous distribution. Nomenclatural Acts japonicus Bernhauer, 1923 (Echiaster), syn.nov. of Echiaster japonicus unicolor Bernhauer, 1922 acutissimus Assing, 2011 (Sclerochiton), spec.nov. barbatus Assing, 2011 (Sclerochiton), spec.nov. bistipulatus Assing, 2011 (Sclerochiton), spec.nov. excisus Assing, 2011 (Sclerochiton), spec.nov. hastatus Assing, 2011 (Sclerochiton), spec.nov. laoticus Assing, 2011 (Sclerochiton), spec.nov. maculosus Assing, 2011 (Sclerochiton), spec.nov. ochraceus Kraatz, 1859 (Sclerochiton), LT now syn. of Sclerochiton indicus Motschulsky, 1858 penicillatus Assing, 2011 (Sclerochiton), spec.nov. rectus Assing, 2011 (Sclerochiton), spec.nov. rougemonti Assing, 2011 (Sclerochiton), spec.nov. schuelkei Assing, 2011 (Sclerochiton), spec.nov. sinuatus Assing, 2011 (Sclerochiton), spec.nov.